Demonstration of nuclear gamma-ray polarimetry based on a multi-layer CdTe Compton camera - S. Go; Y. Tsuzuki; H. Yoneda; Y. Ichikawa; T. Ikeda; N. Imai; K. Imamura; M. Niikura; D. Nishimura; R. Mizuno; S. Takeda; H. Ueno; et al. (Scientific Reports, 2024)
Abstract To detect and track structural changes in atomic nuclei, the systematic study of nuclear levels with firm spin-parity assignments is important. While linear polarization measurements have been applied to determine the electromagnetic character of gamma-ray transitions, the applicable range is strongly limited due to the low efficiency of the detection system. The multi-layer Cadmium-Telluride (CdTe) Compton camera can be a state-of-the-art gamma-ray polarimeter for nuclear spectroscopy with the high position sensitivity and the detection efficiency. We demonstrated the capability to operate this detector as a reliable gamma-ray polarimeter by using polarized 847-keV gamma rays produced by the $$^{56}Fe$$ 56 Fe ( $${ p},{ p'}γ $$ p , p ′ γ ) reaction. By combining the experimental data and simulated calculations, the modulation curve for the gamma ray was successfully obtained. A remarkably high polarization sensitivity was achieved, compatible with a reasonable detection efficiency. Based on the obtained results, a possible future gamma-ray polarimetery is discussed.